Suppressive Effect of Immunization with Mouse Fetal Antigens on Growth of Cells Infected with Rauscher Leukemia Virus and on Plasma-Cell Tumors - Hanna, M. G. (1971)
The recovery of spleen cells infected with Rauscher leukemia virus (RLV) and grown in Millipore diffusion chambers, the development of RLV-induced splenomegaly, and the cumulative mortality from a transplanted ascites plasma-cell tumor were all suppressed in young adult BALB/c male mice previously primed at 3-weekly intervals with x-irradiated, syngeneic embryo cells. RLV-induced splenomegaly was also suppressed by adoptive transfer of postpartal spleen cells, as well as spleen cells for animals primed with syngeneic embryo cells. Similar suppressions were not observed in mice primed with neonatal or normal syngeneic cells. Further, injection of fetal cells was not effective in suppressing the immune function of normal spleen cells, as measured by ability to elaborate a primary immunoglobulin M response to heterologous erythrocyte antigen. The results of this study add to the broad spectrum of tumors of experimental animals and man known to contain neoantigens common to fetal cells.